A phylogenomic look into the systematics of oceanic squids (order Oegopsida). Issue 4 (1st October 2021) - Fernández-Álvarez, Fernando Á; Taite, Morag; Vecchione, Michael; Villanueva, Roger; Allcock, A Louise
Abstract: Oceanic squids of the order Oegopsida are ecologically and economically important members of the pelagic environment. They are the most diverse group of cephalopods, with 24 families that are divergent morphologically. Despite their importance, knowledge of phylogenetic relationships among oegopsids is less than that among neritic cephalopods. Here, we provide the complete mitogenomes and the nuclear 18S and 28S ribosomal genes for 35 selected oceanic squids, which were generated using genome skimming. We performed maximum likelihood and Bayesian inference analyses that included 21 of the 24 oegopsid families. In our analyses, the architeuthid, chiroteuthid and enoploteuthid family groups, which have been proposed previously based on morphological and natural history characteristics, were retrieved as monophyletic. The morphologically divergent Cranchiidae formed a well-supported clade with families Ommastrephidae and Thysanoteuthidae, with a unique mitochondrial gene order. The family Lycoteuthidae was revealed as paraphyletic and contained Pyroteuthidae. Thus, the two lycoteuthid subfamilies are herein elevated to family level, increasing the number of oegopsid squid families to 25. In order to describe the diversity and evolutionary trends of oegopsid squids accurately, the superfamilies Architeuthoidea, Chiroteuthoidea, Cranchioidea and Enoploteuthoidea are resurrected from the literature, and the superfamilies Cycloteuthoidea, Octopoteuthoidea and Pholidoteuthoidea are proposed. The phylogenetic positions of Gonatidae, Histioteuthidae and Onychoteuthidae were not stable in our phylogenetic analyses and are not assigned to a superfamily. This study supports the utility of genome skimming to solve the phylogenetic relationships of oceanic squids.